This new hospital - LeBlang, Ted; Greene, Penny; Marsh, Allen; Woodin, Dale (American Society for Healthcare Engineering of the American Hospital Association Insight Media [distributor], 2008)
Designed to assist hospitals as they build new facilities and renovate existing ones. The elements stressed on this DVD include: assembling the right team, reviewing scope and budgets, up front planning, and continued involvement of the project team.